Incorporating Database Design in Warnier Method - Chand, Donald (Australasian Journal of Information Systems, 2000)
The Warnier method, a highly prescriptive program design approach for file-oriented solutions, has been criticized for its lack of a database design component. This paper addresses this weakness by incorporating a logical database design step in Warnier method. Specifically, the paper presents rules for transforming the information in a Warnier diagram into a set of relations. With this extension the Wamier method complements the entity-relationship approach for data analysis and logical database design.